A Test of the Differential Involvement Hypothesis. (April 2019) - Unnever, James; Owusu-Bempah, Akwasi; Deryol, Rustu
This research draws on longitudinal data from the Project on Human Development in Chicago Neighborhoods (PHDCN) to examine whether African Americans report more trouble with the police than Latinos, Whites, and members of other racial groups after controlling for self-reported offending and other covariates. We tested whether the average self-reports of trouble with the police varied across the neighborhood clusters included within the PHDCN and generated a series of negative binomial models to assess whether African Americans self-reported more trouble with the police than others. The results generated from the unconditional hierarchical model showed that the average self-reports of trouble with the police did not significantly vary across the neighborhoods. The negative binomial results indicate that African Americans report significantly more trouble with the police while controlling for the respondents' levels of offending, level of impulsivity, levels of anxiety and depression, gang membership, their family's criminal involvement, whether they or their parents had serious mental health issues, the respondents' current and expected economic conditions, their racial affinity, as well as other individual characteristics.